An Integrated Mechanistic Model of Mindfulness-Oriented Recovery Enhancement for Opioid-Exposed Mother–Infant Dyads - Reese, Sarah E.; Conradt, Elisabeth; Riquino, Michael R.; Garland, Eric L. (Frontiers in Psychology, 2021)
A growing body of neurobiological and psychological research sheds light on the mechanisms underlying the development and maintenance of opioid use disorder and its relation to maladaptive parenting. Perinatal opioid use is associated with significant maternal distress, as well as increased risk for child maltreatment and impaired developmental outcomes for children. Drawing from extant data, here we provide an integrated mechanistic model of perinatal opioid use, parenting behavior, infant attachment, and child well-being to inform the development and adaptation of behavioral interventions for opioid-exposed mother-infant dyads. The model posits that recurrent perinatal opioid use leads to increased stress sensitivity and reward dysregulation, resulting in decreased perceived salience of infant cues, disengaged parenting behavior, disrupted infant attachment, and decreased child well-being. We conclude with a discussion of Mindfulness-Oriented Recovery Enhancement as a means of addressing pathogenic mechanisms undergirding perinatal opioid use, maladaptive parenting, and attachment deficits, presenting evidence on the efficacy and therapeutic mechanisms of mindfulness. As perinatal opioid use increases in the United States, empirically-informed models can be used to guide treatment development research and address this growing concern.